TINDAK PIDANA DENGAN SENGAJA MEMILIKI BARANG ORANG LAIN BUKAN KARENA KEJAHATAN (STUDI PUTUSAN NOMOR 197/PID.B/2020/PN.BKS) : Criminal Offence Of Deliberately Owning Other People's Goods Not Because Of Crime (Study Of Rulling Number 197/Pid.B/2020/Pn.Bks) - Raden Mas Diaz Ihsanul Mahendra; Vience Ratna Multiwijaya (Reformasi Hukum Trisakti, 2024)
The defendant Aryo Hendarto offered to help Setiawan witness to bring cassette containing money and then the key was given by the witness, after that the defendant opened the cassette with pen and then took a sum of Rp.14,500,000, the defendant had repeatedly taken PT. SSI money with total Rp. 95,000,000,. Study Decision with the main problem Is the actions of the perpetrator of Crime deliberately owning other people's goods not because the crime is appropriate Based on Article 362 of Criminal Code? How the conviction of the perpetrator of criminal appropriate based on Criminal Code? This research conducted normative juridical manner with analytically descriptive and conclusions with deductive nature. Based on the analysis, it concluded 1) application and elements of criminal act not belong based on article 362 of Criminal Code. 2) the conviction of the perpetrator of criminal act only 1 year in prison because in article 372 of the Criminal Code is minimal 4 years prison. The results is in article 372 Jo Article 64 paragraph (1) of the Criminal Code with a maximum of 4 years in prison and because the defendant committed criminal act with a smatter, namely criminal act that continues.